PERAN POLISI LALU LINTAS KEPOLISIAN RESOR KOTA PEKANBARU DALAM MENINDAK PELANGGARAN LALU LINTAS PADA PELAJAR SMP DI PEKANBARU - Tiara Fitra Erisman; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at the Satlantas Polresta Pekanbaru, Kecamatan Senapelan, Pekanbaru. The purpose of this study is to analyze the role of Traffic Police in dealing with violations of the use of motorcycle in junior high school students in Pekanbaru, especially those who take their motorcycle to school. The sampling technique is done by purposive sampling because the writer has set a number of criteria in the selection of subjects as many as 5 people and 3 of them have a special duty in handling traffic violation cases in school students such as elementary, junior high, high school, and college. Data collection methods in this study are observation, in-depth interview and documentation. The results of the study found that traffic violations are carried out by junior high school students who often do not use safety equipment and do not have a driver's license. The acts of prosecution of violations include prevention and eradication. Preventive actions in reducing violations in the use of motorcycle for students in Pekanbaru such as providing good information or counseling to schools from elementary, junior high, high school, also for parents. In addition, Satlantas Polresta Pekanbaru also provided demonstrations regarding Safety Riding in schools, as well as providing information through mass media. As for repressive act, raids were held at certain times by checking the completeness of vehicles and driving licenses and giving tickets as proof of violations.Keywords: middle school students, violation, motorcycle, traffic police